The Effect Of Pgr Kinetin And Coconut Water On The Growth And Development Of The Orchid Dendrobium mirbelianum In Vitro - Tungga, AgnesTheresia; Tilaar, Wenny; Tulung, Stella Maria Theresia; Pongoh, Jantje; Mamarimbing, Rinny; Sumayku, Bertje R. A. (Sam Ratulangi University, 2023)
This research aims to determine the effect of the concentration of ZPT kinetin and coconut water on the growth and development of orchid shoots. This research was carried out at the Biotechnology Laboratory, Faculty of Agriculture, Sam Ratulangi University Manado from May to June 2023. This research used a factorial experiment in a Completely Randomized Design (CRD) with 5 replications consisting of two factors. The first factor is Kinetin concentration; 1 mg/l (K1), 2 mg/l (K2) and 3 mg/l (K3) and the second factor is Coconut Water Composition; Coconut water 10% (A1), Coconut water 20% (A2), Coconut water 30% (A3) and Coconut water 40% (A4). Data were analyzed using ANOVA and if there was a significant effect, it was continued with the 5% BNT test. The variables observed were: shoot height, number of leaves, number of shoots, and wet weight. The results showed that there was a significant effect on the number of shoots on the single factor Kinetin while the others were not significantly different between the combination of Kinetin and coconut water on the growth and development of orchid shoots, namely on the variable height of shoots, number of shoots, number of leaves and percentage of wet weight of Dendrobium orchid shoots mirbelianum. Keywords: Orchid, Dendrobium mirbelianum, Kinetin, Coconut water, In vitro Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh konsentrasi penggunaan ZPT kinetin dan air kelapa terhadap pertumbuhan dan perkembangan tunas anggrek. Penelitian ini dilaksanakan di Laboratorium Bioteknologi, Fakultas Pertanian, Universitas Sam Ratulangi Manado dari bulan Mei sampai Juni 2023. Penelitian ini menggunakan percobaan faktorial dalam Rancangan Acak Lengkap (RAL) dengan 5 ulangan yang terdiri dari dua faktor. Faktor pertama yaitu konsentrasi Kinetin; 1 mg/l (K1), 2 mg/l (K2) dan 3 mg/l (K3) dan faktor kedua Komposisi Air Kelapa; Air kelapa 10% (A1), Air kelapa 20% (A2), Air kelapa 30% (A3) dan Air kelapa 40% (A4). Data dianalisis dengan ANOVA dan jika berpengaruh nyata maka dilanjutkan dengan uji BNT 5 %. Variabel yang diamati adalah: tinggi tunas, jumlah daun, jumlah tunas, dan berat basah. Hasil penelitian menunjukan bahwa terdapat pengaruh nyata terhadap jumlah tunas pada faktor tunggal Kinetin sedangkan yang lain tidak berbeda nyata antara kombinasi kinetin dan air kelapa terhadap pertumbuhan dan perkembangan tunas anggrek yaitu pada variabel tinggi tunas, jumlah tunas, jumlah daun dan persentase berat basah tunas anggrek Dendrobium mirbelianum. Kata Kunci: Anggrek, Dendrobium mirbelianum, Kinetin, Air Kelapa, In vitro